The hills have eyes II - Craven, Wes; Maddalena, Marianne; Locke, Peter; Craven, Jonathan; Weisz, Martin (Beverly Hills, Calif. : Twentieth Century Fox Home Entertainment, 2007)
Two years after the Carter family was attacked, National Guard trainees find themselves in the same secret military testing zone defending themselves against cannibalistic mutants looking for female breeders to continue their line
Title from title screen
Based on the characters created by Wes Craven
Executive producer, Jonathan Debin ; camera, Sam McCurdy ; editing, Kirk Morri, Sue Blainey ; music, Trevor Morris
Cast: Michael McMillian, Jessica Stroup, Daniella Alonso, Jacob Vargas, Flex Alexander, Lee Thompson Young, Eric Edelstein, Michael Bailey Smith
DVD Format
region 1, full screen (1.33:1) and widescreen (2.35:1) presentations; Dolby Digital 5.1 surround, Dolby surround
Keywords: Cannibalism -- Drama; Murder -- Drama; Rape -- Drama